Analysis of lightning vulnerability level in the City of Mataram and surrounding area using the simple additive weighting method - Azany Harits Muhammad; Suardi Iman; Marsono Agus; Ali Munawar; Prayitno Adi Suko (E3S Web of Conferences, 2023)
Mataram City, West Lombok and Central Lombok Regencies are areas that have a high level of infrastructure development. This high level of infrastructure development has indirectly increased the risk of lightning strikes in the city of Mataram and its surroundings. This study aims to determine the level of threat, susceptibility, and vulnerability to lightning strikes in the city of Mataram and its surroundings, and to find a correlation between the increase in land use as buildings and settlements with the increase in the number of lightning strikes. The lightning data was obtained from the monitoring results of the Mataram Geophysics Station in the 2017-2021 period which was processed using the Simple Additive Weighting method. From the processing results, the level of vulnerability to lightning in the very high category is in Selaparang and Mataram sub-districts. The results of the Pearson correlation calculation in an increase in the number of areas used as buildings and settlements to an increase in the number of lightning, obtained 14 districts with high Pearson correlation index values and 3 districts with very high Pearson correlation index values which included Batukliang, Sekotong, and Jonggat Districts.